Magnesium Alloy Effects on Plasma Electrolytic Oxidation Electro-Ceramic and Electro-Coat Formation and Corrosion Resistance. Issue 14 (1st October 2019) - Brady, Michael P.; Leonard, Donovan N.; McNally, Elizabeth A.; Kish, Joseph R.; Meyer, Harry M.; Cakmak, Ercan; Davis, Bruce
Abstract : Plasma electrolytic oxidation (PEO) electro-ceramic (EC) coatings with and without an epoxy-base electro-coat (E-coat) overlayer were studied on four magnesium alloys using the same process deposition parameters: Mg-3Al-1Zn (AZ31B), Mg-9Al-0.5Zn (AZ91D), Mg-1.5Zn-0.3Zr-<0.5Nd (ZE10A, ZEK100 type), and Mg-4Y-(<2.5 Nd)-0.4Zr (WE43). A similar magnesium-fluoride (Mg-F) base EC chemistry formed on all four alloys. However, the morphology of the EC was significantly impacted by the substrate alloys, with higher alloy Al or Zr/rare earth (RE) levels also resulting in thicker coatings. A duplex EC structure formed on AZ31B, AZ91D, and ZE10, with a submicron inner layer and a thicker outer porous layer; whereas a striated multi-layer inner region and thick porous outer region formed on WE43. The EC coated alloys exhibited similar corrosion resistance to the bare alloys due to coating porosity, with the best corrosion resistance exhibited by AZ91D and WE43. After applying the E-coat overlayer, similar, excellent corrosion resistance was exhibited for all four EC + E-coated alloys. Scribing of the EC + E-coat to controllably introduce a coating defect degraded corrosion resistance, particularly for WE43, which suffered from E-coat blistering due to susceptibility of the inner striated EC layer to delamination.